ISLAMIC BANK CUSTOMERS’ ADOPTION OF DIGITAL BANKING SERVICES: EXTENDING DIFFUSION THEORY OF INNOVATION - Shaikh, Imran Mehboob; Amin, Hanudin; Noordin, Kamaruzaman; Shaikh, Junaid Mehboob (Journal of Islamic Monetary Economics and Finance, 2023)
This paper examines the factors that drive non-users of digital banking services rendered by Pakistani Islamic banks to adopt digital banking using the Diffusion theory of Innovation (DOI). We gather data from 208 Islamic bank customers who do not use digital banking services. Findings of the study reveal that adoption of digital services offered by Islamic banks are largely decided by relative advantage, technology self-efficacy and complexity. All the factors above are influential in determining the digital banking adoption by non-users. The finding serves as an essential input to banks and policy makers in expanding the adoption of digital banking services of Islamic banks. Acknowledgment The authors would like to thank Bank Indonesia Institute, Bank Indonesia, for the funding that made this study possible.